Role of trans-cerebellar diameter in estimating gestational age in second and third trimester of pregnancy - Uikey, Prashant Arun; Kedar, Kshama Vivek; Khandale, Surekha Narayan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Uncertain gestational age is associated with higher perinatal mortality rates and an increased incidence of low birth weight and spontaneous preterm delivery. Errors in gestational age estimation can lead to iatrogenic neonatal morbidity from prematurity. Precise determination of gestational age antenatally is a boon to modern obstetrics in context with improved neonatal survival. The most effective way to date pregnancy is by sonography. Several parameters can be considered for estimation of gestational age trans-cerebellar diameter is one such parameter. The objective of this study was to study the role of fetal trans-cerebellar diameter in estimating the gestational age in second and third trimester of pregnancy and its correlation with gestational age, BPD, HC, AC and FL. The design of this study was to hospital based prospective cohort study conducted at department of obstetrics of Government medical College Nagpur, over a period of 1 year. Methods: 500 women with sure dates between 7 and 11 weeks of gestation were booked. First trimester USG using crown rump length for confirmation of gestational age was done. These patients were advised to come for follow up till 40 weeks of gestation and repeat USG was done in second and third trimester. Trans-cerebellar diameter was correlated with expected gestational age with CRL, BPD, HC, AC and FL in weeks. Results: 98.56% of variability in gestational age could be explained by variation in trans-cerebellar diameter (TCD) only. Addition of other variables did not make any significant difference indicating that TCD alone is the strong predictor of gestational age. Conclusions: Normative cerebellar measurements throughout pregnancy permit estimation of gestational age independent of the shape of fetal head and also offer potential for evaluating abnormal fetal growth and anomalous development of central nervous system.